High-temperature electrical measurements and thermodynamic properties of Fe3O4-FeCr2O4-MgCr2O4-FeAl2O4 spinels - Nell, J; Wood, B (1991)
Electrical conductivity and thermopower measurements have been made on Fe3O4-FeCr2O4, Fe3O4-MgCr2O4, and Fe3O4-FeCr2O4-FeAl2O4 spinel solid solutions at 600°C to 1400°C and 1 atm. The thermopower and electrical conductivity data were combined with earlier results on the joins Fe3O4-MgFe2O4, Fe3O4-FeAl2O4, and Fe3O4-MgAl2O4 to estimate cation distributions for compositions within the geologically important system (Mg2+,Fe2+)-(Fe3+,Al3+,Cr3+)2O4. The cation distributions were then combined with activity-composition relations and interphase partitioning data to derive a complete thermodynamic model for the complex system (Mg2+,Fe2+)(Fe3+,Al3+,Cr3+)2O4. -Authors